(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
A large part of Latvia pig fa rm with their equipment for removal of manue are badly acting on the surrounding environment. To install the depositeries for manue with the necessary capacity at existing pig farms require the capital investments about 7-10 million lats. When the depositories are built, it is important to improve the system of manue removing in order not to allow to liquefy the mass of the manue. Examination of pig farms resulted in working out the measures to decrease the liquefying of the manue. Experiments were carried out in a finishing pig farm with 1200 pigs. The liquid fraction was separated from the excrements. For removing out the dense manue with humidity of 86-88 % a scraper-transporter had been used. In the farm in question this measure has decreased the liquefying 2,5-3 times. Calculations and analyses of the expenses have showed, that the smallest (approximately 5 lats/pig per year) they are if pigs are kept on slatted floors. The total expenses to build the premises in this case are by 20 % less.